2013
DOI: 10.1177/0011000012470569
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Dating Violence on Adolescent Girls’ Educational Experiences

Abstract: The purpose of this study was to investigate the impact of dating violence on adolescent girls' educational experiences and relationships with peers, family members, and school personnel. We used a constructivist-interpretivist research paradigm and conducted semistructured interviews with 19 adolescent female participants who experienced abuse from a dating partner during the past year. Using grounded theory analytical methods, findings included identification of specific types of abuse girls experienced in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…Although White (1982), in a meta-analytic review, found that SES was only weakly associated with academic achievement, our results were consistent with previous literature suggesting a link between IPV and poorer academic achievement for our rural adolescents (Bergman, 1992; Chronister et al, 2014; Cleveland et al, 2003; Halpern et al, 2001). Grade distributions differed from A- or B-level average grades for females who were not victims to C-level grades or below on average for those who were.…”
Section: Discussionsupporting
confidence: 92%
“…Although White (1982), in a meta-analytic review, found that SES was only weakly associated with academic achievement, our results were consistent with previous literature suggesting a link between IPV and poorer academic achievement for our rural adolescents (Bergman, 1992; Chronister et al, 2014; Cleveland et al, 2003; Halpern et al, 2001). Grade distributions differed from A- or B-level average grades for females who were not victims to C-level grades or below on average for those who were.…”
Section: Discussionsupporting
confidence: 92%
“…Although several studies have examined psychological, behavioral, and developmental consequences of adolescent dating violence victimization (e.g., Banyard and Cross, 2008; Button and Miller, 2013; Chronister et al, 2014; Collibee and Furman, 2014; Foshee et al, 2013; Holmes and Sher, 2013; Teten et al, 2009; Ulloa et al, 2014), very few have examined injury as a consequence. This study is a first step in addressing gaps in the field related to understanding injuries sustained by victims of dating violence.…”
Section: Discussionmentioning
confidence: 99%
“…Teenagers that experience or have been exposed to dating violence are more likely to exhibit some of these behaviors: withdrawal, poor sleep, depression, anxiety, suicidal thoughts, aggressive behaviors to peers, substance abuse, early onset-sexual activity, have multiple dating and sexual partners, exhibit rude and anomaly behaviors in school [6,22] and at home [8,15,19]. The overall academic performance of the teen drops [14] and there is irregular school and class attendance with the sole intention of spending time with their partner [6].…”
Section: Signs Of Exposure To Dating Violencementioning
confidence: 99%